Cruciferae of provincia de La Pampa (Argentine) (Semiárida, 2020)
The present paper is a contribution to the understanding of the flora of the province of La Pampa, Argentina. The objective is to facilitate the identification of the Cruciferae (Brassicaceae) genera and species of their that grow in this province. This family is represented here by 24 genera and 40 native and adventive species. Keys and brief descriptions of genera and species are provided for their identification. The most important characteristics are iIIustrated.
Keywords: Cruciferae; Brassicaceae; La Pampa